New approaches for extracting and recovering metals from mine tailings - Falagán, Carmen; Grail, Barry M.; Johnson, D. Barrie (Minerals engineering, 2017)
[Display omitted] •Mineral tailings from two copper mines were bioleached under different conditions.•Greatest copper extraction was achieved at extremely low pH, at 45°C and under oxidative/reductive conditions.•Copper present in tailings PLS was selectively precipitated as CuS by biogenic H2S.•Microbial communities were dominated by Sb. thermosulfidooxidans and Acidithiobacillus spp.•The microbial community composition was affected by temperature and the tailings used. Waste materials from metal mining, such as mineral tailings, often contain significant amounts of potentially valuable metals particularly where, as in many historic operations, the efficiency of flotation technologies used to concentrate target minerals was not as good as those currently available. A two-stage mineral leaching and metal recovery protocol was developed to extract copper from tailings generated as waste materials in two mines currently operating in Spain and Serbia. The most effective extraction of copper (84 to >90%) was achieved by bioleaching the tailings at 45°C, using a defined microbial consortium, where elemental sulfur was added to the tailings and the pH of leach liquors allowed to fall to ∼pH 1, at which point anaerobic conditions were imposed. The thermo-tolerant acidophiles Acidithiobacillus caldus and Sulfobacillus thermosulfidooxidans emerged as the dominant bacteria present in both tailings leachates under these conditions. Copper present in the pregnant leach solutions (PLS) produced were next precipitated as a sulfide phase using hydrogen sulfide generated in a low pH (4.0) sulfidogenic bioreactor. The off-line system used allowed the copper present in PLS to be precipitated selectively without the need to adjust the pH of the PLS, though small amounts of silver present in PLS from one of the tailings samples co-precipitated with copper sulfide. Experimental data also suggested that it would be possible to extract silver from bioleached solid residues (where it was mostly found) using a simple chemical extractant. The results suggested that bio-processing these waste materials would have economic as well as environmental benefits.